New energy power generation power control method and device, terminal equipment and storage medium - YI YANG; XU ZHANPENG; MIAO LU; CHEN KUIYE; YANG CHENG; GU YICAN; ZHANG XINGZI; LIU HAOYI; YANG ZHENNAN (2025)
The invention discloses a new energy power generation power control method and device, terminal equipment and a storage medium. The method comprises the steps that the current output power, the load demand power and the predicted power generation power of power generation equipment are acquired; calculating the target output power of the power generation equipment according to the current output power, the predicted power generation power and the load demand power; and according to the target output power, generating a corresponding output power control instruction so as to adjust the output power of the power generation equipment. Predicted generation power is introduced, and the target output power is calculated in combination with the current output power and the load demand power. Due to instability of the new energy power generation system, the target output power obtained through calculation can better adapt to power generation fluctuation at the future moment, system response lag or insufficient adjust